From Classrooms to Clicks: Perceptions of Technology-Mediated Summative English Testing among Vocational Students - Syafrayani, Putri Rizki; Meisuri (EDUCATION JOURNAL OF INDONESIA, 2025)
The transition to technology-mediated assessment in education has reshaped testing practices globally, yet its implications for vocational students remain underexplored. This study investigates vocational learners’ perceptions of summative English testing conducted through digital platforms, focusing on the perceived benefits and drawbacks. Drawing on a mixed-methods approach, data were collected through questionnaires and interviews with students from a vocational institution. The findings reveal a complex interplay between usability, fairness, and performance impact. While some students appreciated the efficiency and immediate feedback of digital tests, many expressed concerns over interface unfamiliarity, limited digital literacy, and heightened test anxiety, which they felt adversely affected their performance. These perceptions were further influenced by socioeconomic and educational backgrounds, suggesting potential inequities in assessment outcomes. The study highlights the need for more inclusive and accessible digital assessment designs tailored to the vocational context. Implications for educators and policymakers include the integration of digital literacy support and the development of student-centered testing platforms to enhance validity and fairness in language evaluation.